Rule of Law, Islam, and Constitutional Politics in Egypt and Iran, The - Brown, Nathan J.; Arjomand, Said Amir (Book collections on Project MUSE., 2013)
In the early years of the twenty-first century, Egypt and Iran have been beset with demands for fundamental change. This book draws together leading regional experts to provide a penetrating comparative analysis of the ways Islam is entangled with the process of democratization in authoritarian regimes. By comparing Islam and the rule of law in these two nations, one Sunni and Arab-speaking, the other Shi'ite and Persian-speaking, this volume enriches the current debate on Islam and democracy, making for a more nuanced understanding and appreciation of differences with the Muslim world, and provides an indispensible background for understanding the Green movement in Iran since 2009 and the Egyptian revolution of 2011. -- From publisher's website.